Photovoltaic properties of a heterostructure on the basis of porous silicon and polyaniline - Stakhira, P.; Aksimentieva, E.; Mykytyuk, Z.; Cherpak, V. (Functional Materials, 2005)
An electric junction between porous silicon (n-type conductivity) and conductive polyaniline (p-type conductivity) has been made by electrochemical polymerization of aniline on the porous silicon surface. This heterostructure has been found to exhibit rectifying І-V characteristics. Under illumination, a considerable increase of the current is observed with a reverse bias. The structure photosensitivity is defined mainly by two barriers, namely, by the polymer/porous silicon interphase and the porous silicon/crystalline silicon barrier.